The Neuropsychological Basis of Lexically-based Language Teaching - Siusana Kweldju (TEFLIN Journal: A publication on the teaching and learning of English, 2004)
This paper proposes a lexically-based approach for the teaching of English in Indonesia. To develop the approach, neurolinguistic and psycholinguistic research findings for L2 learning are reviewed because this approach has to consider how human mind stores, processes, recognizes and retrieves words. Neurobiologically, the learning of L1 is different from L2. Thus, the lexically-based approach gives more emphasis on chunking, the learning of formulaic phrases, and conscious awareness of learning.